Corporatizing Rural Education Neoliberal Globalization and Reaction in the United States - Cervone, Jason A. (New Frontiers in Education, Culture, and Politics, 2018)
This book presents a critical analysis of the anti-democratic and pro-authoritarian ideologies that exist in rural communities in the United States. The author book also explores and recontextualizes existing research in rural education within this anti-democratic framework, as well as theorizing the consequences of this ideology as it takes place in the rural United States, specifically in regards to the physical and ideological shaping of rural communities to meet the needs of capitalist accumulation. Finally, it discusses the ways rural youth can reclaim the public sphere within their communities through critical education. .